Pulp tissue from primary teeth: new source of stem cells - Paloma Dias Telles; Maria Aparecida de Andrade Moreira Machado; Vivien Thiemy Sakai; Jacques Eduardo Nör (University of São Paulo, 2011)
SHED (stem cells from human exfoliated deciduous teeth) represent a population of postnatal stem cells capable of extensive proliferation and multipotential differentiation. Primary teeth may be an ideal source of postnatal stem cells to regenerate tooth structures and bone, and possibly to treat neural tissue injury or degenerative diseases. SHED are highly proliferative cells derived from an accessible tissue source, and therefore hold potential for providing enough cells for clinical applications. In this review, we describe the current knowledge about dental pulp stem cells and discuss tissue engineering approaches that use SHED to replace irreversibly inflamed or necrotic pulps with a healthy and functionally competent tissue that is capable of forming new dentin.